Foragers in the middle Limpopo Valley : trade, place-making, and social complexity - Forssman, Tim, (Cambridge monographs in African archaeology ;, 2020)
Foragers were present in the Limpopo Valley (South Africa) before the arrival of farmers and not only witnessed but also participated in local systems leading to the appearance of a complex society. Despite numerous studies in the valley, forager involvement in socio-political developments has been, until now, largely ignored.